Papilledema and abducens nerve palsy associated with vitamin B12 deficiency - Singh, Navnoor; Fernandes, Warren; Fernandes, Bolivia C. A. (International Journal of Advances in Medicine, 2022)
Papilledema is defined as optic disc swelling that is secondary to elevated intracranial pressure. Vision is usually well preserved with this condition. The optic discs appear blurred in papilledema. Elevation in intracranial pressure is due to variety of reasons of which intracranial hemorrhage is the most common. We present a case in which our patient developed papilledema due to vitamin B12 deficiency. Lateral rectus muscle palsy occurs due to abducens nerve palsy. The lateral rectus muscle is responsible for lateral movement of the eyeball, specifically abduction. Its palsy results in sudden onset of horizontal double vision, which is worse when the patient looks to the affected side. There is also limited outward movement of the affected eye. Abducens nerve palsy can occur due to ischemia injury, stroke, infection, brain tumour, elevated intracranial pressure, or inflammation of the nerve. In our patient the abducens nerve palsy was due to homocysteinemia secondary to dietary vitamin B12 deficiency. Homocysteine is a potent atherosclerotic risk factor and can cause ischemic nerve palsy, as seen in our patient.